Analysis of palm oil plantation regional regulation implementation in bangka belitung from an economic law perspective - Gunawan, Arifin Faqih (Institute for Law and Economics Studies, 2025)
This study examines the implementation of Regional Regulation Number 19 of 2017 in Bangka Belitung Province, which mandates palm oil farmers to integrate cattle farming into plantation management. The research employs a normative-empirical legal approach, combining analysis of legal frameworks with field research. Primary data was collected through semi-structured interviews with 30 smallholder farmers and 10 local government officials between January-June 2023, focusing on implementation challenges and compliance factors. Secondary data included regional regulations, implementation reports, and official correspondence, analyzed using qualitative content analysis methods. The study reveals several implementation barriers: lack of sanctions, high initial costs, limited technical knowledge, and insufficient government support. Analysis of interview transcripts and documents, conducted through systematic coding and thematic analysis, indicates significant challenges for smallholder farmers, particularly financial constraints and inadequate incentives. The findings demonstrate that weak supervision and policy design compromise the regulation's effectiveness. The study recommends incorporating sanctions, providing financial assistance, implementing technical training programs, and enhancing monitoring mechanisms. These recommendations aim to improve compliance and align the regulation with its objectives of economic growth and environmental sustainability. This research contributes to understanding how legal frameworks can better support sustainable agricultural practices while considering farmers' socio-economic conditions